Indirect diplomacy across Europe: The encounters of Antonio Rincón and Hieronymus Laski in the 1520s - Tamus, Elvira (Librosdelacorte.es, 2024)
European politics in the 1520s were determined by the Valois–Habsburg competition for dominion over Italy and the Habsburg–Ottoman rivalry in the Central European region and the Mediterranean. In this complex situation, diplomatic actors played a crucial role in the decision–making process by gathering and transmitting information, preparing and forming alliances, as well as providing various services to nurture existing relations and create new ones. Yet, this individual agency of these actors is far from thoroughly explored in historiography. This contribution looks at the ways in which Antonio Rincón, the Spanish envoy of Francis I of France, and Hieronymus ?aski, the Polish envoy of John I of Hungary, established and nurtured contacts as well as gathered information in order to lay the foundations of a coalition against the Habsburgs. This actor–centred approach aims to shed light on the contribution of individual agency to anti-Habsburg diplomacy in the early sixteenth century.